PELATIHAN PENGOLAHAN STICK JAGUNG DAN ES KOLANG KALING DI DESA TRIDHARMA KECAMATAN PULUBALA KABUPATEN GORONTALO - Bait, Yoyanda; Rachman, Agus Bahar (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
The aim of implementing the training activities for processing corn sticks and kolang kaling ice is to increase the skills of PKK mothers and young women. The training method is in 2 ways, namely lectures and practice. Evaluation of program success through observation of participant participation. The training activity was held on October 22, 2022 in the Tridharma Village Office Hall with 15 participants, PKK women and young women. This activity is integrated with KKN-Thematic. Based on the results of observations, this activity succeeded in increasing the knowledge of PKK mothers and young women regarding the processing of corn sticks and kolang kaling ice.